STRATEGI RANCANGAN DESAIN PROMOSI LAYANAN PANGGILAN DARURAT 112 INDONESIA - Ramadhianto Tri Handoko; Drajatno Widi Utomo; Achmad Syarief (Universitas Trisakti, 2023)
AbstractPromotional Design Strategy Of 112 Indonesia Emergency Call Service. Case Study: Design Scenario For The Introduction And Promotion Of Indonesia's 112 Emergency Calling Service To Generation Z. The 112 Emergency Call Service Program, which is an integrated service, has been running since 2016 in Indonesia. From 40 random respondents, it was found that only 52.5% of the people knew about the Emergency Call Service (Call Center) 112. In fact, according to the results of interviews with the Ministry of Communications and Informatics, Kominfo hopes that the level of public understanding is at least 80%. The reason is that every region in Indonesia has not been fully integrated. The problems that occur are: (a) there is no proper design to become a means of introducing and promoting the 112 Emergency Call Service To Generation Z, and (b) there is still a lack of a design promotion strategy for the 112 Emergency Call Service To Generation Z. The objectives of the research are: (1) drafting a document on the awareness dissemination strategy or the introduction of the Emergency Call Service 112 To Generation Z, (2) producing a design that is in accordance with the awareness dissemination strategy or the introduction of the Emergency Call Service 112 To Generation Z. The research method used is qualitative with focused interviews. The design method for the campaign is the Design Thinking method with 5 stages namely; (i) Emphasize, (ii) Define, (3i) Ideate, (iv) Prototype, and (v) Test. From the results of this study, 3 content pillars can be created, namely: (1) Educative Content, (2) Reels Instagram Video, and (3) Awareness Content. Each pillar content has its own purpose to the audience. This research process is still the first strategy that will be suggested to the Indonesian 112 Emergency Call Service, so it is necessary to carry out A/B testing to see which strategy is effective for implementing the introduction promotion strategy. When the research strategy was tested, the respondents’ results were tested whether they were inline with expectations or not. If most of them answered no, this research process would be repeated to get the appropriate results.Keywords: emergency call service 112, emergency call 112, call center 112, design thinking